PERSPEKTIF ISLAM TERHADAP PENGEMBANGAN KOMPETENSI SUPERVISI MANAJERIAL DAN AKADEMIK PENGAWAS - Jamilus Jamilus (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
This discussion aims to describe the Islamic perspective on the development of supervisory managerial and academic supervisory competencies. This is important because the teachings of Islam have universal concepts and principles related to supervision or supervision and their competencies. Managerial supervision that emphasizes supervision and regulation of all elements in the education unit and academic supervision which is more in the form of assistance and guidance to teachers in improving the effectiveness of the process and learning outcomes, both require a number of competencies that must be developed continuously. Based on the Islamic perspective, then in its application managerial supervision competence must be based on the nature of Allah SWT al-Raqîb which means supervising and other traits in relation to being the regulator or manager of the universe with all its contents. While academic supervision competencies based on Islamic perspectives should prioritize the principle of helping to ease the burden and difficulties faced by others.